Discovery of the type-II superconductor Ta_{4}Rh_{2}C_{1−δ} with a high upper critical field - KeYuan Ma; Sara López-Paz; Karolina Gornicka; Harald O. Jeschke; Tomasz Klimczuk; Fabian O. von Rohr (Physical Review Research)
We report on the discovery of superconductivity in the previously unknown compound Ta_{4}Rh_{2}C_{1−δ}. Ta_{4}Rh_{2}C_{1−δ} crystallizes in the η-carbide structure type, in the cubic space group Fd3[over ¯]m (No. 227) with a unit cell parameter of a=11.7947 Å. Temperature-dependent magnetic susceptibility, resistivity, and specific-heat capacity measurements reveal that Ta_{4}Rh_{2}C_{1−δ} is a type-II bulk superconductor with a critical temperature of T_{c}=6.4K and a normalized specific-heat jump ΔC/γT_{c}=1.56. Notably, we find that Ta_{4}Rh_{2}C_{1−δ} has a high upper critical field of μ_{0}H_{c2}(0)=17.4T, which exceeds the BCS weak-coupling Pauli limit of μ_{0}H_{Pauli}=11.9T.